PENOBATAN SERTA PERANAN TENGKU HUSEIN SEBAGAI SULTAN PERTAMA SINGAPURA-JOHOR 1819-1824 - Khairunisa Umaira; Isjoni Isjoni; Bedriati Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Singapore was originally founded as a British trading settlement in 1819. At the beginning of the 19th century, the British were looking for a suitable place for trading in the region that could counterbalance the Dutch influence at that time. Under the leadership of Sir Thomas Stamford Raffles, the British officially opened a trading village on the coast of Singapore on February 6, 1819. In the mission of opening a new port, the British needed strength and approval from the residents of the local island who were part of the Kingdom of Johor and were also allies of the Dutch. So the British chose Sutan Mahmud Syah III's first son, Tengku Husein, to be the first Sultan of Singapore by taking advantage of the internal conflicts that occurred within the Kingdom of Johor. The objectives of this research are 1) To find out the background of Tengku Husein being crowned the Sultan of Singapore-Johor 1819-1824, 2) To find out that Singapore was chosen as the place for Tengku Husein's coronation, 3) To know the process of Tengku Husein's coronation as Sultan of Singapore-Johor, 4 ) To determine the influence of the British in the government of Tengku Husein. The method used in this research is a qualitative approach. The research location is in Tanjung Pinang, Riau Islands. The results of the study show the coronation and the role of Tengku Husein as the first sultan of Singapore-Johor.Key Words: History, Kingdom of Johor, First Sultan of Singapore.